Effect of niacin supplementation of stockers grazing tall fescue pastures - F.K. Brazle; K.P. Coffey; L.R. Corah; Joseph L. Moyer (Kansas Agricultural Experiment Station Research Reports, 1990)
In three trials, there was no gain response by stockers offered supplemental niacin while grazing tall fescue pasture in the spring or fall. There was a trend toward lower body temperatures for niacin-supplemented cattle, but this was not significant. Niacin fed at 2 to 4 g per head daily did not reduce the fescue endophyte fungus problem.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Niacin; Fescue; Endophyte; Stockers